Inventor Diasporas and the Internationalization of Technology - Miguelez, Ernest (Published by Oxford University Press on behalf of the World Bank, 2019)
This paper documents the influence of diaspora networks of highly-skilled individuals—that is, inventors—on international technological collaborations. Using gravity models, it studies the determinants of the internationalization of inventive activity between a group of industrialized countries and a sample of developing and emerging economies. The paper examines the influence exerted by skilled diasporas in fostering cross-country co-inventorship as well as R&D offshoring. The study finds a strong and robust relationship between inventor diasporas and different forms of international co-patenting. However, the effect decreases with the level of formality of the interactions. Interestingly, some of the most successful diasporas recently documented—namely, Chinese and Indian ones—do not govern the results.